Pengelolaan Sampah Botol Plastik Melalui Bank Sampah TPST 3R, Trirejo, Loano, Purworejo - Faoziyah Nuraini; Septy Widyati; Widiyah Tri Ramadani; Nur Ngazizah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
. A waste bank is a place for processing waste using a banking mechanism. Waste management at TPST 3R Tri Guyup Rukun Trirejo village has implemented the 3R principle (Reuse, Reduce, Recycle) in managing waste at the community level. The aim of this research is to determine the mechanism of waste processing and the role of waste banks in dealing with waste problems that occur in society. The data collection technique in this research uses qualitative methods. The results of observations and interviews show that TPST 3R Tri Guyup Rukun, Trirejo village, is a waste bank that processes organic and non-organic waste originating from the community's sorted waste. With the existence of 3R Tri Guyup Rukun TPST, the community can experience significant benefits for their daily lives, one of which is earning income. So it can be concluded that banks have an important role in managing community waste.